Penerapan Strategi Pembelajaran Berbasis Proyek pada Mata Pelajaran Ekonomi Kelas XI dalam Konteks Pendidikan Kristen [The Application of Project-Based Learning Strategies in Grade XI Economics Subjects in the Context of Christian Education] - Caroline Isabell Novianti; Selvi Esther Suwu (Universitas Pelita Harapan, 2026)
The implementation of the Merdeka Belajar curriculum in Indonesia gives students the freedom to choose several major subjects that they are interested in and allows students to interact with new friends in certain subjects, including the economics subject. Although this is a good thing, teenage students often feel uncomfortable being in a new environment with new people to study with. Christian education aims to provide holistic growth to students, including in their ability to communicate and collaborate with others and to have a Christian worldview. As images of God, humans are created to have relationships with one another through interaction, communication, and collaboration in reflecting God's relational love in His Trinity, so that humans can achieve mutual prosperity through each individual's contribution to the community. In guiding students toward this truth, a project-based learning strategy is applied to improve students' collaborative skills in economics lessons. Project-based learning strategies are generally carried out in groups to achieve a specific goal so that this strategy is expected to be able to foster students' collaboration skills as preparation for them to enter college or the workforce.